Photocatalytic reduction of Cr(VI) from aqueous solution by visible light/CuO-Kaolin: Optimization and modeling of key parameters using central composite design (CCD). Issue 7 (3rd May 2021) - Mohagheghian, Azita; Besharati-Givi, Naghmeh; Godini, Kazem; Dewil, Raf; Shirzad-Siboni, Mehdi
ABSTRACT: In the current research, a visible light photocatalytic method, in which the CuO/Kaolin nanocomposite photocatalyst was utilized to reduce Cr(VI), was investigated. Response surface methodology was applied to determine the influence of various variables (individual effect and correlated effects) and the optimum conditions for Cr(VI) reduction. Analysis of variance (ANOVA) indicated a high coefficient of determination value (R 2  = 0.9812) for the developed second-order regression model, suggesting the suitability of the model. Approximately 99.99, 95.77 and 79.6% of Cr(VI) in a synthetic water, drinking water and electroplating wastewater samples were reduced, respectively.